Penerapan Metode Guru Kunjung Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Materi Perbandingan Di Kelas IV SDN 004 Batu Ampar Kota Batam - Aini, Nur (Universitas Muhammadiyah Magelang, 2021)
The purpose of this study is to improve students' learning outcomes in comparative material math subjects with the teacher's methods. This study consists of two cycles, in order to break the student's learning outcomes from pre-bullying conditions, cycles I and II also to find out the supporting factors and inhibition of student learning outcomes in comparative material mathematics subjects. The results showed that pre-cycle learning results were 46,6 %, cycle to I results averaged 73,2% and cycle II results were 86,6%. Thus it can be asked successfully and reach the indicator determined by the researcher, which is 80% completion. Based on the results of the study it can be concluded that the application of teacher methods increases learning outcomes. There are many types of data that are concluded to solve this research problem is to use the method of the visiting teacher by using the tanjun teacher method. From the results of the study it can be concluded that by using the method of the teacher visiting in calculating comparisons and can increase the value of learners' learning outcomes in accordance with the expected goals and values through KKM